The Effectiveness of Nasal Conformers in Patients with Unilateral Cleft Lip and Palate Following Primary Cheiloplasty: A Systematic Review and Meta-Analysis - Chimruang, Jutharat; Worasakwutiphong, Saran; Tansalarak, Ratchawan (Archives of Plastic Surgery, 2025)
This study aims to evaluate the effectiveness of nasal conformers in patients with unilateral cleft lip and palate (UCLP) following primary cheiloplasty.We conducted a comprehensive search in PubMed, EMBASE, the Cochrane Central Register of Clinical Trials (CENTRAL), and EBSCO Open Dissertation from inception to November 2023. We included three retrospective and one prospective cohort studies evaluating the effect of postoperative nasal conformers after primary cheiloplasty. Data extraction and risk of bias assessment were performed using the Risk of Bias in Non-Randomized Studies of Intervention (ROBINS-I) tool. A meta-analysis was conducted using a random-effects model to pool data and determine overall effect sizes with a 95% confidence interval (CI). The mean difference (MD) was calculated for nostril height and nostril width outcomes. The study was registered with PROSPERO (CRD42024511395).The four included studies represented 83 treated patients and 84 controls. The overall quality of studies was moderate, as assessed by the ROBINS-I tool. Meta-analysis results showed that nostril width was wider on the cleft side compared with controls (MD = 1.10; 95% CI: 0.64, 1.56), while nostril height was lower on the cleft side (MD = −0.73; 95% CI: −1.20, −0.26). Ratios for nostril width and nostril height were generally closer to symmetry.This study suggests that nasal conformers may improve nasal symmetry in patients with UCLP following primary cheiloplasty. Further research, including randomized controlled trials and long-term follow-up studies, is needed to confirm these findings and refine the use of nasal conformers in clinical practice.
Keywords: Cleft Lip; nasal stents; systematic review; meta-analysis